Heterogeneity of Multiple Sclerosis White Matter Lesions Detected With T2*‐Weighted Imaging at 7.0 Tesla. Issue 5 (6th February 2015) - Yao, Bing; Ikonomidou, Vasiliki N.; Cantor, Fredric K.; Ohayon, Joan M.; Duyn, Jeff; Bagnato, Francesca
ABSTRACT BACKGROUND AND PURPOSE Postmortem studies in multiple sclerosis (MS) indicate that in some white matter lesions (WM‐Ls), iron is detectable with T2*‐weighted (T2*‐w), and its reciprocal R2* relaxation rate, magnetic resonance imaging (MRI) at 7.0 Tesla (7T). This iron appears as a hyperintense rim in R2* images surrounding a hypointense core. We describe how this observation relates to clinical/radiological characteristics of patients, in vivo. METHODS We imaged 16 MS patients using 3T and 7T scanners. WM‐Ls were identified on T1‐w/T2‐w 3T‐MRIs. Thereafter, WM‐Ls with a rim of elevated R2* at 7T were counted and compared to their appearance on conventional MRIs. RESULTS We counted 36 WM‐Ls presenting a rim of elevated R2* in 10 patients. Twenty‐three (64%) lesions coincided with focal WM‐Ls on T2‐w MRIs; 13 (36%) coincided with only portions of larger lesions on T2‐w images; and 20 (56%) corresponded to a hypointense chronic black hole. WM‐Ls presenting a rim of elevated R2* were seen in both relapsing‐remitting patients with low disability and in those with long‐standing secondary progressive MS. CONCLUSIONS WM‐Ls with a contour of high R2* are present at different MS stages, potentially representing differences in the contribution of iron in MS disease evolution.